Deuterium Isotope Effect on the Dissociation of Weak Acids in Water and Deuterium Oxide - Robinson, R. A. (J Res Natl Bur Stand A Phys Chem, 1969)
The dissociation constants of o-nitroanilinium ion, m-nitroanilinium ion, and 4-chloro-2,6-dinitrophenol in deuterium oxide at 25 °C have been determined by a spectrophotometric method, and an emf method has been used to obtain (pK(1) + pK(2))/2 for citric acid in deuterium oxide. In addition, data for the dissociation constants of other weak acids in ordinary and heavy water have been critically examined with a view to clarifying the relationship between the deuterium isotope effect and the intrinsic strength of the acid. The difference ΔpK between the pK value in deuterium oxide and that in water varies linearly with pK above pK = 7. Two stronger inorganic acids (sulfuric and phosphoric) also appear to lie on an extension of this same line. On the contrary, a considerable group of organic acids with pK less than 7 have values of ΔpK that are more or less constant near ΔpK = 0.55. It appears, therefore, that the isotope effect is more complex than has heretofore been assumed.